The Influence of Flexible Working Hours, Work From Home, Work Stress, and Salary on Employee Performance at PT Armada Auto Tara during COVID-19 Pandemic - Leni Yuliati; Patrick Alexander Wilhelm Smith; Sekar Wulan Prasetyaningtyas (Quantitative Economics and Management Studies, 2023)
This study aims to analyze the effect of Flexible Working Hours, Work From Home, Work Stress, and Salary on Employee Performance at PT. Armada Auto Tara during the COVID-19 pandemic. The data collection method used is by distributing questionnaires to employees at PT. Armada Auto Tara. After the questionnaires were distributed to 110 employees, validity and reliability tests were carried out to determine the feasibility of the questionnaires. Determination of the sample using the purposive sampling method and the Slovin formula where the formula allows a researcher to take a sample of the population with the desired level of accuracy (Stephanie, 2013). The data management is carried out using SPSS software and goes through several stages, namely multiple linear regression analysis, f statistic test, and t statistical test. The results of the analysis show that the first hypothesis, namely Flexible Working Hours, has no effect on Employee Performance. The second hypothesis is that Work From Home shows a significant positive effect on employee performance. The third hypothesis is that work stress shows no effect on employee performance. The fourth hypothesis is that salary shows a significant positive effect on employee performance.